Production and properties of alpha-glucosidase from Lactobacillus acidophilus. - Li, K B (1983)
Lactobacillus acidophilus IFO 3532 was found to produce only intracellular alpha-glucosidase (alpha-D-glucoside glucohydrolase; EC 3.2.1.20). Maximum enzyme production was obtained in a medium containing 2% maltose as inducer at 37 degrees C and at an initial pH of 6.5. The enzyme was formed in the cytoplasm and accumulated as a large pool during the logarithmic growth phase. Enzyme production was strongly inhibited by 4 microM CuSO4, 40 microM CoCl2, and beef extract; MnSO4 and the presence of proteose peptone and yeast extract in the medium greatly enhanced enzyme production. A 16.6-fold purification of alpha-glucosidase was achieved by (NH4)2SO4 fractionation and DEAE-cellulose column chromatography. The enzyme showed high specificity for maltose. The Km for alpha-p-nitrophenyl-beta-D-glucopyranoside was 11.5 mM, and the Vmax for alpha-p-nitrophenyl-beta-D-glucopyranoside hydrolysis was 12.99 mumol/min per mg of protein. The optimal pH and temperature for enzyme activity were 5.0 and 37 degrees C, respectively. The enzyme activity was inhibited by Hg2+, Cu2+, Ni2+, Zn2+, Ca2+, Co2+, urea, rose bengal, and 2-iodoacetamide, whereas Mn2+, Mg2+, L-cysteine, L-histidine, Tris, and EDTA stimulated enzyme activity. Transglucosylase activity was present in the partially purified enzyme, and isomaltose was the only glucosyltransferase product. Amylase activity in the purified preparation was relatively weak, and no isomaltase activity was detected.